2016
DOI: 10.5897/jphe2016.0811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Brucella antibodies in horses (Equus Caballus) in Jalingo, Taraba State, Nigeria

Abstract: A study was conducted to determine the prevalence of Brucella antibodies in Jalingo using the Rose Bengal plate test (RBPT) and the serum agglutination test (SAT). A total of 90 adult horses that were on zero grazing management system were sampled. The sampling sites were selected based on the availability of horses. The objectives of the study were to determine the prevalence of Brucella antibodies in horses as well as the distribution of the infection according to sex. There was no association of horses seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Therefore, despite differences in timing, environment and host determinants, diagnostic tests, sampling size and study designs, the prevalence of brucellosis in the Iranian horses is almost the same, and the seroprevalence of brucellosis is expected to be less than 10% across Iran. In the studies conducted in other countries, the seroprevalence of brucellosis were reported to be 0—100% in Nigeria (Ardo & Abubakar, 2016; Ardo et al., 2016; Bertu et al., 2014; Ehizibolo et al., 2011; Sadiq et al., 2013), 8.3% in Mongolia (Zolzaya et al., 2014), 0.26–6.5% in Brazil (Antunes et al., 2013; Santos et al., 2016), 3.6‐ ‐67.9% in Pakistan (Gul et al., 2013; Hussain et al., 2020; Safirullah et al., 2014), 0.25–60.6% in Turkey (Göz et al., 2007; Solmaz et al., 2004; Tel et al., 2011), 0.24% in Mexico (Acosta‐Gonzalez et al., 2006), 3.6–4.9% in Sudan (Musa, 2004), 1–8.5% in Jordan (Abo‐Shehada et al., 2009) and 0% in Eritrea (Omer et al., 2000). This significant difference in the prevalence of brucellosis in different countries, and even between different regions in a country can be due to differences in management such as husbandry, contact rate with domestic and wild animals and population density, location, climate, sample size, diagnostic method and hosting characteristics (Acosta‐Gonzalez et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite differences in timing, environment and host determinants, diagnostic tests, sampling size and study designs, the prevalence of brucellosis in the Iranian horses is almost the same, and the seroprevalence of brucellosis is expected to be less than 10% across Iran. In the studies conducted in other countries, the seroprevalence of brucellosis were reported to be 0—100% in Nigeria (Ardo & Abubakar, 2016; Ardo et al., 2016; Bertu et al., 2014; Ehizibolo et al., 2011; Sadiq et al., 2013), 8.3% in Mongolia (Zolzaya et al., 2014), 0.26–6.5% in Brazil (Antunes et al., 2013; Santos et al., 2016), 3.6‐ ‐67.9% in Pakistan (Gul et al., 2013; Hussain et al., 2020; Safirullah et al., 2014), 0.25–60.6% in Turkey (Göz et al., 2007; Solmaz et al., 2004; Tel et al., 2011), 0.24% in Mexico (Acosta‐Gonzalez et al., 2006), 3.6–4.9% in Sudan (Musa, 2004), 1–8.5% in Jordan (Abo‐Shehada et al., 2009) and 0% in Eritrea (Omer et al., 2000). This significant difference in the prevalence of brucellosis in different countries, and even between different regions in a country can be due to differences in management such as husbandry, contact rate with domestic and wild animals and population density, location, climate, sample size, diagnostic method and hosting characteristics (Acosta‐Gonzalez et al.…”
Section: Discussionmentioning
confidence: 99%